Renal cell carcinoma with inferior vena cava thrombus extending to the right atrium diagnosed during pregnancy. (June 2017) - Ghanney, Efe C.; Cavallo, Jaime A.; Levin, Matthew A.; Reddy, Ramachandra; Bander, Jeffrey; Mella, Maria; Stone, Joanne; Schwartz, Myron; Haines, Kenneth; Gidwani, Umesh; Mehrazin, Reza
Only one case of renal cell carcinoma (RCC) with inferior vena cava (IVC) tumor thrombus diagnosed and treated during pregnancy has been reported in the literature. In that report, the tumor thrombus extended to the infrahepatic IVC (level II tumor thrombus). In the present case, a 37-year-old woman with lupus anticoagulant antibodies was diagnosed with RCC and IVC tumor thrombus extending to the right atrium (level IV tumor thrombus) at 24 weeks of pregnancy. The fetus was safely delivered by cesarean section at 30 weeks of gestation. At 4 days later, an open right radical nephrectomy and IVC and right atrial thrombectomy were performed on cardiopulmonary bypass (CPB) once the patient's hemodynamic status had been optimized. Fetal and maternal concerns included the risk of a thromboembolic event (due to increased hypercoagulability from pregnancy, active malignancy, and lupus anticoagulant), intraoperative hemorrhage risk (due to extensive venous collaterals and anticoagulation), and fetal morbidity and mortality (due to fetal lung immaturity). Standardized guidelines for treatment of RCC with or without IVC tumor thrombus during pregnancy are unavailable due to the infrequency of such cases. Treatment decisions are therefore individualized and this case report may inform the management of future patients diagnosed with RCC with level IV tumor thrombus during pregnancy.